Pendidikan Inklusi: Integrasi Konsep Konstruktivistik Vygotsky dan Landasan Al-Qur'an untuk Mendukung SDGs 4 - Ashoumi, Hilyah; Yusuf, Moh Asror (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
Students with special needs often face discrimination in formal education, posing a challenge for the Indonesian government to ensure equitable and fair education for all. Inclusive education serves as a strategic approach to providing quality education access for everyone, supporting the achievement of SDG 4 on inclusive and quality education. This study aims to examine inclusive education from the perspective of Lev Vygotsky's constructivist learning theory and Islamic principles to explore their relevance to the principles of the Sustainable Development Goals (SDGs). The research employs a library research method. The findings reveal that Lev Vygotsky's constructivist theory, particularly the Zone of Proximal Development (ZPD), significantly contributes to inclusive education. ZPD emphasizes social interaction and teacher guidance as key elements of learning, promoting collaboration, active student engagement, and dynamic learning processes. The implementation of this theory fosters an inclusive learning environment that values diversity. Islamic values, as reflected in QS An-Nisa verse 58 and QS Al-Hujurat verse 13, support justice, trustworthiness, and respect for diversity, aligning with the principles of inclusive education and Vygotsky's theory. These verses underline the importance of justice, social interaction, and collaboration for holistic human development. The implications of this study highlight the need for teacher training to implement collaborative learning based on ZPD and strengthen the values of justice and respect for diversity within the curriculum. This supports the creation of inclusive, fair, and quality education in line with SDG 4.